Acute syphilitic posterior placoid chorioretinitis: a case report: Akutni sifilitični posteriorni plakoidni horioretinitis: prikaz primera - Skitek, Petra (Acta Medico-Biotechnica, 2021)
Purpose: To present a case of acute syphilitic posterior placoid chorioretinitis (ASPPC), one of the possible ocular manifestations of syphilis, and alert clinicians to the reemergence of syphilis worldwide.Methods: Clinical findings, fluorescein angiography, indocyanine green angiography, autofluorescence imaging, time domain optical coherence tomography features, and management of the patient are presented.Results: A 39–year–old male presented as an otherwise healthy man with a 3–day history of blurred vision in his right eye. Clinical examination revealed signs of posterior uveitis. Clinical features and additional imaging findings were consistent with the descripton of ASPPC. Syphilis was confirmed with a positive serological test for syphilis. Additional human immunodeficiency virus (HIV) testing was intended and the patient only then disclosed his medical history of being HIV positive and receiving antiretroviral therapy. Cerebrospinal fluid examination revealed neurosyphilis. He was treated with a 2– week course of intravenous penicillin and his visual acuity recovered fully.Conclusions: Ocular findings may be the presenting feature of syphilis. Physicians' awareness of the variety of clinical presentations of syphilis is important for prompt recognition and early management of this curable disease, which can cause substantial morbidity and increased mortality if left untreated.
Keywords: syphilis; chorioretinitis; fluorescein; indocyanine green angiography